1999
DOI: 10.1523/jneurosci.19-20-08979.1999
|View full text |Cite
|
Sign up to set email alerts
|

Bovine CNS Myelin Contains Neurite Growth-Inhibitory Activity Associated with Chondroitin Sulfate Proteoglycans

Abstract: The absence of fiber regrowth in the injured mammalian CNS is influenced by several different factors and mechanisms. Besides the nonconducive properties of the glial scar tissue that forms around the lesion site, individual molecules present in CNS myelin and expressed by oligodendrocytes, such as NI-35/NI-250, bNI-220, and myelin-associated glycoprotein (MAG), have been isolated and shown to inhibit axonal growth. Here, we report an additional neurite growth-inhibitory activity purified from bovine spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(150 citation statements)
references
References 57 publications
5
143
0
2
Order By: Relevance
“…The myelin fraction contains low-density lipids that are derived from axonal myelin sheaths. The presence of brevican in this fraction has already been reported (Seidenbecher et al 1998;Niederöst et al 1999) and it was suggested to contribute to the nonpermissive properties of CNS myelin (Niederöst et al 1999). The light membrane fraction is a less well defined membrane subpopulation, which contains a mixture of endoplasmic reticulum, Golgi and plasma membranes as estimated by electron microscopy (Cohen et al 1977;Hu et al 1998).…”
Section: Discussionmentioning
confidence: 81%
“…The myelin fraction contains low-density lipids that are derived from axonal myelin sheaths. The presence of brevican in this fraction has already been reported (Seidenbecher et al 1998;Niederöst et al 1999) and it was suggested to contribute to the nonpermissive properties of CNS myelin (Niederöst et al 1999). The light membrane fraction is a less well defined membrane subpopulation, which contains a mixture of endoplasmic reticulum, Golgi and plasma membranes as estimated by electron microscopy (Cohen et al 1977;Hu et al 1998).…”
Section: Discussionmentioning
confidence: 81%
“…P0 -P1 rat DRG explants were grown on myelin-coated coverslips in the absence or presence of 10 or 25 AM EGCG. Myelin was prepared from adult rat spinal cords as described (Niederost et al, 1999). For myelin substrate assays, wells of a four-well tissue culture dish were precoated with 20 Ag/ ml poly-l-lysine for 2 h at RT.…”
Section: Tissue Culture Assaysmentioning
confidence: 99%
“…Multiple inhibitors have been identified in myelin (McKerracher et al, 1994;Mukhopadhyay et al, 1994;Niederost et al, 1999), and one of the most potent inhibitors may be Nogo (Caroni and Schwab, 1988a;Chen et al, 2000;GrandPre et al, 2000;Prinjha et al, 2000). This contention is supported by experiments showing that treatment with the inhibitor neutralization (IN-1) antibody, which recognizes Nogo-A, enhanced neurite outgrowth and functional recovery after CNS spinal cord injuries in rats (Caroni and Schwab, 1988b;Schnell and Schwab, 1990).…”
mentioning
confidence: 94%